Analysis and optimization of periodic inspection intervals in cold standby systems using Monte Carlo simulation. (October 2018) - Alebrant Mendes, Angelica; Weber Lorenzoni, Matheus
Highlights: Cold standby redundant systems are widely applied in processes requiring high reliability. Periodic inspections are employed to verify the components' condition and prevent system failures. Monte Carlo simulation is used to analyze and optimize the time interval between periodic inspections. The optimization considers the required availability and the lowest cost possible. This method has the ability of considering any probability distribution. Abstract: Cold standby redundant systems are widely applied in processes requiring high reliability. When continuous monitoring is not possible, periodic inspections are employed to verify the components' condition and prevent system failures. This paper aims to develop a Monte Carlo simulation model to analyze and optimize the time interval between periodic inspections in cold standby systems considering the required availability and the lowest cost possible. Times-to-system-failure and their respective total cost per cycle were modeled and simulated. After determining the simulation error, a sensitivity analysis was conducted in order to verify the parameters effects in the optimal time interval between inspections. As a result, a simulation model was developed and can be used to optimize time intervals between periodic inspections of different cold standby systems. The main advantage of this method is the ability of considering any probability distribution to represent the times-to-failure and times-to-repair, not being limited to the exponential distribution.